Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/lary.28466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Abdominal Dermal‐Fat Grafting to Repair Parotidectomy Defects: An 18‐Year Cohort Study

Abstract: ObjectivesTo assess the outcomes of abdominal dermal‐fat grafting following superficial and total parotidectomy.MethodsA retrospective chart review of parotidectomy patients was performed. Patients were divided into four groups based on surgical extent and grafting status: superficial parotidectomy (SP), superficial parotidectomy with grafting (SPg), total parotidectomy (TP), and total parotidectomy with grafting (TPg). Complication rates and operative times were then compared between surgically matched groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…In particular, it is readily available from multiple potential donor sites (e.g., abdominal wall), and it could be easily harvested without prolonging operative time. Donor site complications are uncommon, 47,58 and the scar could be easily hidden. Moreover, no increase in post-operative complication at the level of the parotid bed was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it is readily available from multiple potential donor sites (e.g., abdominal wall), and it could be easily harvested without prolonging operative time. Donor site complications are uncommon, 47,58 and the scar could be easily hidden. Moreover, no increase in post-operative complication at the level of the parotid bed was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, graft-related complications (e.g., graft necrosis) are extremely rare, and are significantly related to graft site adjuvant radiotherapy. 58 On the other hand, the main limit of fat allografting is the unpredictable reabsorption rate, which may vary from 20% to 90% of the volume. 84,85 Transplantation with dermis or an overcorrection between 15% and 30% have been used to overcome this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our clinical practice, where most total parotidectomy patients are offered abdominal dermal fat graft reconstruction. We have found that it is a relatively simple and effective reconstructive option that is not associated with increased operative time or complication rates 44 …”
Section: Discussionmentioning
confidence: 98%
“…We have found that it is a relatively simple and effective reconstructive option that is not associated with increased operative time or complication rates. 44 Eye tracking has been used previously to investigate multiple facial deformities, including facial paralysis 27 and Mohs defects. 25 We can compare our frontal view results to these studies (also displayed frontal images for 10 seconds) to provide relative effect sizes.…”
Section: Discussionmentioning
confidence: 99%